Tailoring of processing parameters for sintering microsphere‐based scaffolds with dense‐phase carbon dioxide1. Issue 2 (31st October 2012) - Jeon, Ju Hyeong; Bhamidipati, Manjari; Sridharan, BanuPriya; Scurto, Aaron M.; Berkland, Cory J.; Detamore, Michael S.
Abstract: Microsphere‐based polymeric tissue‐engineered scaffolds offer the advantage of shape‐specific constructs with excellent spatiotemporal control and interconnected porous structures. The use of these highly versatile scaffolds requires a method to sinter the discrete microspheres together into a cohesive network, typically with the use of heat or organic solvents. We previously introduced subcritical CO2 as a sintering method for microsphere‐based scaffolds; here we further explored the effect of processing parameters. Gaseous or subcritical CO2 was used for making the scaffolds, and various pressures, ratios of lactic acid to glycolic acid in poly(lactic acid‐co‐glycolic acid), and amounts of NaCl particles were explored. By changing these parameters, scaffolds with different mechanical properties and morphologies were prepared. The preferred range of applied subcritical CO2 was 15–25 bar. Scaffolds prepared at 25 bar with lower lactic acid ratios and without NaCl particles had a higher stiffness, while the constructs made at 15 bar, lower glycolic acid content, and with salt granules had lower elastic moduli. Human umbilical cord mesenchymal stromal cells (hUCMSCs) seeded on the scaffolds demonstrated that cells penetrate the scaffolds and remain viable. Overall, the study demonstrated the dependence of the optimal CO2 sintering parameters on the polymer and conditions, and identified desirable CO2 processing parameters to employ in the sintering of microsphere‐based scaffolds as a more benign alternative to heat‐sintering or solvent‐based sintering methods. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.